Plug-in hybrid conversion of three wheeler using a novel drive strategy. (1st January 2012) - Amjad, Shaik; Rudramoorthy, R.; Neelakrishnan, S.; Gurusubramanian, Sabarish; Dheepan Raja, J.; Mathew, Renjit; Sundaravel, M.
In Asia, three-wheelers (auto rickshaws) represent a very important mode of intermediate public transport and serving as an effective feeder to the mass transport system. However, the significant contribution to pollution levels by three wheelers has demanded for a possibility of a future solution to ensure better air standards in urban areas where the population of auto rickshaws are higher. Interest is growing in plug-in hybrid technology that offers advantages of clean and more efficient vehicles compared to the current hybrids. In this paper, the development of a novel energy management strategy suitable for Indian city driving conditions for a converted plug-in hybrid auto rickshaw is discussed. The automatic switching strategy incorporated in the control system of the plug-in hybrid auto rickshaw enables the vehicle to offer better fuel economy and advantages of lower emission, by minimising the idling and slow power running regions of an internal combustion engine. The vehicle's energy management strategy has been tested with the various modes for the plug-in hybrid auto rickshaw. The implementation of plug-in hybrid concept with a novel drive strategy for three-wheelers will lead to reduction of urban emissions and hence better air quality for Indian cities and also provides much cheaper public transportation system.